Dynamic simulation modelling using descriptive information in natural language. (10th March 2009) - Takahashi, Yutaka
In business contexts, people on site have various information such as rules and experience-based knowledge. Although dynamic simulations utilise such information, they are less frequently employed by business people than other methods. Supposing that the mathematical expressions in dynamic simulation models shun business people, this paper suggests a middle language, which is an intermediary to translate from descriptive information in natural language to dynamic simulation models. It utilises not only numerical data but also descriptive information. In particular, this modelling method is useful in making 'as-is' models. In the last section, an application of this method is shown.